Trimetazidine in chronic heart failure patients aged above 75 years - I. V. Ignatenko; A. L. Pirogov; D. A. Altman; A. S. Prazdnov; N. K. Vereina (Кардиоваскулярная терапия и профилактика, 1970)
Aim. То assess 12-week trimetazidine therapy (Preductal® MB, 70 mg/d) effects on clinical status, quality of life (QoL), endothelial function, and myocardial contractility in chronic heart failure (СHF) and coronary heart disease (CHD) patients aged above 75 years. Material and methods. In total, 110 patients aged 75-89 years (78 men, 42 women) with Functional Class (FC) II-III СHF were examined. All participants were divided into two groups: Group I (intervention; n=55) and Group II (control; n=55). Group II received standard СHF therapy. Group I - stable standard therapy, plus Preductal® MB. Two-stage study program included basic clinical, laboratory and instrumental examination. QoL was assessed with Minnesota Questionnaire, depression questionnaire CES-D, and integral health score. Results. Significant СHF PC reduction, physical stress tolerance increase, QoL and myocardial contractility improvement were registered in СHF patients aged above 75 years, with endothelial function improvement in intervention group. Conclusion. Three-month Preductal® MB treatment (70 mg/d) improves clinical status: reduces СHF and CHD PC, improves QoL. The medication increases myocardial contractility and normalizes endothelial function.